High-Prevalence Stunting in Preschool Children (1–5 Years) Attending Selected Health Centers in a Food Rich Area-Bushenyi District Southwestern Uganda - Douglas Mugarura; Herbert Izo Ninsiima; Hellen Kinyi; Ejike Daniel Eze; Sam Tumwesigire; Prossy Mbekeeka; Andrew Ndamira (Journal of Nutrition and Metabolism)
The prevalence of stunting among children in Uganda and Sub-Saharan Africa is still high, and if Uganda is to achieve the food-related Sustainable Development Goals (SDGs), it must urgently invest in improving nutrition and sanitation. In a food rich area like Bushenyi, chronic undernutrition could be due to several other factors than mere scarcity of food. The Objective(s). This study was carried out to determine the prevalence and socioclinical factors responsible for chronic undernutrition (stunting) among preschool children aged 1–5 years in selected Health facilities in Bushenyi district. Methodology. This was a cross-sectional study assessing the prevalence of stunting and its associated factors among children aged 1–5 years attending selected health centers in Bushenyi District. Data was collected using a pretested questionnaire, taking anthropometric measurements (height/length), and stool analysis for eggs of soil-transmitted helminthes. Prevalence of stunting was presented as percentages. Logistic regression with adjusted prevalence ratio was performed to test the association between the sociodemographic and clinical factors and stunting at bivariate levels of analysis. Results. Most of the children were female, with a median age of 2.1 years and resided in semiurban areas of Bushenyi with their parents. Prevalence of stunting was 89.3%. Only 10.7% of the children were infested with soil-transmitted helminthes. Children likely to be stunted were those who drank unboiled water and were exclusively breastfed. Conclusion. There is a high prevalence of chronic malnutrition in Bushenyi district associated with parents’/care takers’ low level of knowledge.